2020
DOI: 10.3390/w12061595
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rainfall Intensities and Duration on SCS-CN Model Parameters under Simulated Rainfall

Abstract: The Soil Conservation Service curve number (SCS-CN) method has been widely used in rainfall-runoff modelling; however, the direct effects of rainfall intensities and duration, which are major factors in hydrological engineering design, on its parameters (initial abstraction ratio (λ) and potential maximum storage (S), the latter is transformed into curve number (CN)) have seldom been studied. In this study, we chose simulated rainfall experiments on runoff plots (30 mm/h, 180 min; 60 mm/h, 90 min; 90 mm/h, 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Chin (2021) demonstrated that rainfall distribution is essential in determining the appropriate CN value across the United States Curve number for runoff estimating in interlocking concrete pavement of America territory. Our results also agree with the other study (Wang & Bi, 2020) that used a rainfall simulator at a plot scale to demonstrate the effect of rainfall intensity and duration on Q, S, CN, and λ.…”
Section: /13supporting
confidence: 92%
“…Chin (2021) demonstrated that rainfall distribution is essential in determining the appropriate CN value across the United States Curve number for runoff estimating in interlocking concrete pavement of America territory. Our results also agree with the other study (Wang & Bi, 2020) that used a rainfall simulator at a plot scale to demonstrate the effect of rainfall intensity and duration on Q, S, CN, and λ.…”
Section: /13supporting
confidence: 92%
“…For small catchments, it requires the recording of rainfall-runoff events at a high frequency. Some researchers [43] report that the runoff from catchment Q and the initial abstraction (I a ) vary according to the rainfall intensity and duration. In the event of a greater, more intense and shorter rainfall, the runoff generation time is earlier, and the infiltration is lower.…”
Section: Discussionmentioning
confidence: 99%
“…Despite wide applications of the CN method, some watersheds have been found to exhibit significant differences between observed and predicted runoff using the CN method ( Hawkins 2014 ; Muche et al, 2019a ). The effects of rainfall volume, intensity, and frequency ( Muche et al, 2019a ; Wang and Bi 2020 ), in addition to the seasonality of rainfall-runoff relationship could be among the contributing factors to the CN method’s low accuracy in those watersheds ( Rodríguez-Blanco et al, 2012 ). To increase the accuracy of CN generated runoff, Silveira et al (2000) incorporated automated estimation of antecedent moisture using five days of lagged rainfall.…”
Section: Introductionmentioning
confidence: 99%